Förderung einer umweltfreundlichen Verkehrsmittelwahl durch die Emotionalisierung angebotsseitiger Infrastruktur. Eine verkehrswissenschaftliche Analyse unter Berücksichtigung von designorientierten und psychologischen Einflussfaktoren. - Hofmann, Dominic (My University, 2018)
Die Arbeit befasst sich primär mit der Wirkung von produktsprachlichen Faktoren umweltfreundlicher Verkehrsmittel und deren Infrastrukturen auf Nutzende. Dabei wird die Wirkung anhand von Emotionen untersucht. Um dieses Ziel zu erreichen, wurde eine Kombination aus qualitativen und quantitativen wissenschaftlichen Methoden gewählt. Insgesamt wurden im Rahmen der Arbeit 27 Experteninterviews durchgeführt und mehr als 700 Personen befragt. Es zeigt sich, dass die Thematik der Wirkung von Design im Bereich umweltfreundlicher Verkehrsmittel in der Wissenschaft als auch in der Praxis in der Vergangenheit vernachlässigt wurde. Lediglich Teilaspekte oder übergeordnete Begriffe wurden in die Modelle der Verkehrsmittelwahl einbezogen. Die Arbeit identifiziert produktsprachliche Faktoren, welche speziell bei umweltfreundlichen Verkehrsmitteln das Potenzial besitzen, eine Emotion beim Nutzenden auszulösen. So wird aufgezeigt, welche Relationen zwischen produktsprachlichen Faktoren und Emotionen einen besonderen Stellenwert im gesamten Planungs- und Umsetzungsprozess haben sollten, um eine maximale emotional-positive Wirkung beim Nutzenden zu erzielen. Die Arbeit legt auch dar, ob und welche Unterschiede sich bei dem Vergleich der Daten von Nutzergruppen mit soziodemografischen Unterschieden beobachten lassen. Zusammenfassend lässt sich festhalten, dass die in dieser Arbeit entwickelte Methodik eine Möglichkeit bietet, die komplexen Zusammenhänge zwischen der Produktsprache und Emotionen quantitativ zu erfassen. Auch wird aufgezeigt, welche Relationen ein Potenzial bieten, das Verkehrsmittel bzw. die Infrastruktur noch emotional positiver wirken zu lassen.

The present paper deals primarily with the impact of product language factors of environmentally friendly transport vehicles and their infrastructures on users. The effect is examined on the basis of emotions. In order to achieve this goal, a combination of qualitative and quantitative scientific methods was chosen, primarily resulting in expert interviews and the analysis of a quantitative user survey. The survey scheme and the results of the quantitative survey were verified by a validation survey and could be confirmed methodically and in terms of content. Within the framework of this dissertation, a total of 27 expert interviews were conducted and more than 700 persons were interviewed. In general, it can be seen that impact of design on the field of environmentally friendly transport has been neglected in science and practice. Only partial aspects or superordinate terms were included in some models of modal choice. The present paper cannot quantify the exact influence of design on modal choice, but the surveys reveal the general significance of this factor for users. In addition, the paper demonstrates at which point in modal choice product language factors have an influence on the final decision for or against the usage of a transport vehicle or its infrastructure. For the quantitative surveys, it was necessary to break down the components of design into generally understandable product language categories so that the factors were tangible for the respondents. This was achieved with the support of a product language expert. The study identifies product language factors that have the potential to trigger an emotional response for the users of environmentally friendly transport modes or transport infrastructure. Thus it shows which relations between product language factors and emotions should have a special significance in the entire process of planning and implementation in order to achieve a maximum emotional-positive effect on the user. Additionally, the study explains observable differences when comparing the data of various user groups. For example, product language elements have a different emotional effect on younger people than on older people. A trend in gender-specific differentiation is also identified. The extent of the emotional effect always depends on the respective location of the survey. However, there are also clear general tendencies, which can be used to define statements, which are independent of transport mode and location. In summary, the methodology developed in this work, creates an approach to quantitatively grasp the complex connections between product language and emotions. It also shows which relations offer the potential to make the transport vehicles or infrastructure appear even more emotionally positive. This effect ultimately also decides whether a transport mode of the motorized individual transport or an environmentally friendly transport mode is chosen. Thus, this paper provides a basis for discussion and decision making in order to assign a place value for the role and effects of design with regard to environmentally friendly transport modes.
Keywords: Verkehr; Umweltfreundlichkeit; Verkehrsmittelwahl; Verkehrsverhalten; Verkehrsinfrastruktur; Verkehrsmittel; Gestaltung; Design; Wahrnehmung; Einflussfaktor; Emotion; Verkehrspsychologie; Verkehrsplanung; Stadtplanung; ÖPNV; Empirische Untersuchung; Befragung; Begehung